Operation of mobile sensors for monitoring municipal drinking water distribution systems - Rasekh, Amin; Wu, Ruoxi; Wan Salim, Wan Wardatul Amani; Banks, Margaret Katherine (American Society of Civil Engineers, 2014)
Tremendous advances have been recently made in inline, mobile sensors (IMS)technology for monitoring water distribution systems at unprecedentedly high spatial resolutions. Once fully matured, IMSs can be applied to obtain previously inaccessible information about the critical water quality parameters, faults, and leakages inside the pipeline networks. Timely, costefficient, and effective application of IMSs during normal and emergency conditions, however, requires development of models that are able to accurately simulate and optimize their operation in complex and dynamic environment of municipal drinking water networks. This paper describes an ongoing project for development of decision support models for design, planning and operation of mobile sensor networks. They help understanding how modifying different design parameters such as sensors’ measurement sensitivity and battery life enhance system monitoring performance. The models will aid water utilities to identify the best configuration and operation of mobile sensor networks for their systems through informing the cost-benefit analyses.